A Phone Consultation Call Line to Support SBIRT in Pediatric Primary Care - Levy, Sharon; Fuller, Alyssa; Kelly, Shawn; Lunstead, Julie; Weitzman, Elissa R.; Straus, John H. (Frontiers in Psychiatry, 2022)
Background: Screening Brief Intervention Referral to Treatment (SBIRT) is recommended as a routine part of pediatric primary care, though managing patients with positive screens is challenging. To address this problem, the state of Massachusetts created a call line for pediatric Addiction Medicine specialists to provide consultations to primary care providers and access to a behavioral health counselor specially trained in managing adolescent substance use. Objective: To describe the uptake and outcomes of a consultation call line and virtual counseling for managing substance use disorders (SUD) in pediatric primary care. Methods: Service delivery data from consultations and counseling appointments were captured in an electronic database including substance, level of care recommendations and number of counseling appointments completed for each patient. Summary data is presented here. Results: In all, there were 407 encounters to 108 unique families, including 128 consultations and 279 counseling visits in a one-year period. The most common substances mentioned by healthcare providers were cannabis (64%), nicotine (20%), alcohol (20%), vaping (9%) and opioids (5%). Management in primary care was recommended for 87 (68%) of the consultations. Medications for SUD treatment were recommended for 69 (54%) consultations including two for opioid use disorder. Conclusion: We found that both a statewide consultation call line and virtual counseling to support SBIRT in pediatric primary care were feasible. The majority of consultations resulted in recommendations for treatment in primary care.